Thin-Shelled PEGylated Perfluorooctyl Bromide Nanocapsules for Tumor-Targeted Ultrasound Contrast Agent - Achmad, Arifudin (Contrast Media Mol Imaging, 2018)
Shell thickness determines the acoustic response of polymer-based perfluorooctyl bromide (PFOB) nanocapsule ultrasound contrast agents. PEGylation provides stealth property and arms for targeting moieties. We investigated a modulation in the polymer formulation of carboxy-terminated poly(d,l-lactide-co-glycolide) (PLGA) and poly(d,l-lactide-co-glycolide)-block-polyethylene glycol (PLGA-b-PEG) to produce thin-shelled PFOB nanocapsules while keeping its echogenicity, stealth property, and active targeting potential. Polymer formulation contains 40% PLGA-PEG that yields the PEGylated PFOB nanocapsules of approximately 150 nm size with average thickness-to-radius ratio down to 0.15, which adequately hindered phagocytosis. Functionalization with antibody enables in vitro tumor-specific targeting. Despite the acoustic response improvement, the in vivo tumor accumulation was inadequate to generate an observable acoustic response to the ultrasound power at the clinical level. The use of PLGA and PLGA-PEG polymer blend allows the production of thin-shelled PFOB nanocapsules with echogenicity improvement while maintaining its potential for specific targeting.